Hubungan Perhatian Orang Tua dengan Motivasi Belajar Siswa Kelas V SD - adnan,K Adnan,K; muh. Idris jafar; muhammad irfan; Mia Islamia Askal (JPPSD: Jurnal Pendidikan dan Pembelajaran Sekolah Dasar, 2022)
This study aims to determine the relationship between parental attention and learning motivation of fifth grade students of SD Cluster XVIII, Lilirilau District, Soppeng Regency. The approach used is a quantitative approach. The type of research used is descriptive research. The population in this study amounted to 58 students. Data collection was carried out by means of a questionnaire. The data analysis technique used is the person product moment correlation technique. The results showed that the parents' attention and learning motivation of fifth grade elementary school students in Gugus XVIII, Lilirilau District, Soppeng Regency were included in the medium category and there was a significant relationship based on the results of tcount greater than ttable, so the alternative hypothesis (H1) was accepted while the hypothesis (Ho ) rejected.